STONE COMPOSITION PATTERN OF KIDNEY STONE - Alpendri, Aries; HR, Danarto (Indonesian Journal of Urology, 2013)
Objective: The purpose of this study was to know the bacterial and sensitivity pattern towards antimicrobials on kidney stones and to know the stone composition of kidney stones. Material &Method: Data were collected from medical record in 1 year period from January until Desember 2008 with descriptive study design. Results: We found 59 patients in that period, 32 males and 27 females, the mean age was 52,5 ± 10,31 with age 31 – 75 years old, most patients came from Bantul (16,9%) and 25,4% patients were housewives. From urine analysis we found leucocyturia (44,1%), erythrocyturia (39,0%), nitrituria (3,4%) and bacteriuria (6,8%). Urine culture showed E. coli (12,5%) and Candida (12,5%) being the most common causative microorganism. No antimicrobials was sensitive to all bacteriae while all antifungal was sensitive to candida. Stone composition showed ammonium (98%), calcium oxalate (91,8%), calcium non oxalate (93,9%), carbonate (22,4%), cholesterol (14,3%), uric acid (10,2%) and phosphate acid (10,2%). Conclusion: The most common stone composition were ammonium, calcium oxalate, and calcium non oxalate. E. coli still being the most common causative microorganism.Keywords: Kidney stone, stone composition, urinary tract infection, urine analysis, urine culture.